Development of Innovative Chewable Gel Tablets Containing Nutmeg Essential Oil Microcapsules and Their Physical Properties Evaluation - Inga Matulyte; Mindaugas Marksa; Jurga Bernatoniene (MDPI AG, 2021)
Chewable gel tablets are a dosed pharmaceutical form, which can have an active substance, pharmacological effect, or value of nutrition. The texture of these tablets is soft, springy, flexible, and elastic-this is influenced by the chosen ingredients. The aim of this study was to prepare chewable gel tablets with nutmeg essential oil-loaded microcapsules and determine the volatile compounds released from this pharmaceutical form. Gel tablets were prepared by using gelatin as basis, nutmeg essential oil as active compound, and natural ingredients: thyme-sugar syrup, thyme extract, and citric acid as taste and color additives. Texture properties were measured by a texture analyzer. The release of volatile compounds from nutmeg essential oil and gel tablets were analyzed by headspace-gas chromatography with mass spectroscopy in control and artificial saliva conditions in vitro. Nutmeg essential oil microcapsules had influence on the gel tablet's physical properties (p < 0.05, by comparing tablets without glycerol and relative sample with glycerol); glycerol protects the tablets from the formation of sugar crystals on top and keeps good physical parameters (p < 0.05). A total of 12 volatile compounds were identified in nutmeg essential oil, and the six compounds with the highest amounts were selected as controls. Gel tablets prolong the release time of volatile compounds and reduce the amount of the compounds compared to the microcapsules (p < 0.05).